2012
DOI: 10.1039/c2cp24032g
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of methylamine on nitrogen atom modified Mo(100): a density functional theory study

Abstract: Three possible pathways for C-N bond breaking in methylamine have been investigated over clean Mo(100) and nitrogen atom-modified Mo(100) surfaces with a nitrogen coverage of 0.25 monolayer (ML) (N-Mo(100)) firstly, and the C-N bond breaking following the intramolecular hydrogen transfer from the CH3 to NH2 is excluded owing to the high barriers. Then methylamine decomposition starting with C-H, N-H, and C-N scission over the nitrogen atom-modified Mo(100) surface with a nitrogen coverage of 0.5 ML (2N-Mo(100)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…As displayed in Fig.5, the possible reaction pathways of methanol decomposition on Ru(0001) surface can be described as 9CH 3 OH→3CH 3 O+6CH 2 OH+9H→6CH 2 O+ 3CHOH+18H→7CHO+COH+CH+OH+26H→8CO+C+O+ 36H. Interestingly, during methanol decomposition, CHOH is the species most likely to break a C-O bond, similar to the phenomena observed during ethanol decomposition on Pt surfaces [28] and methylamine decomposition on 2N-Mo(100) [29] and Ru(0001) [30] surfaces, i.e., CH 3 CO and CH 2 CO are the species most likely to break the C-C bonds in ethanol, and CNH 2 , CHNH 2 and CHNH are the most likely intermediates formed on 2N-Mo(100) and Ru(0001) surfaces that activate the C-N bond in methylamine. …”
Section: Potential Energy Surfaces(pess) and Reaction Mechanisms On Tsupporting
confidence: 62%
“…As displayed in Fig.5, the possible reaction pathways of methanol decomposition on Ru(0001) surface can be described as 9CH 3 OH→3CH 3 O+6CH 2 OH+9H→6CH 2 O+ 3CHOH+18H→7CHO+COH+CH+OH+26H→8CO+C+O+ 36H. Interestingly, during methanol decomposition, CHOH is the species most likely to break a C-O bond, similar to the phenomena observed during ethanol decomposition on Pt surfaces [28] and methylamine decomposition on 2N-Mo(100) [29] and Ru(0001) [30] surfaces, i.e., CH 3 CO and CH 2 CO are the species most likely to break the C-C bonds in ethanol, and CNH 2 , CHNH 2 and CHNH are the most likely intermediates formed on 2N-Mo(100) and Ru(0001) surfaces that activate the C-N bond in methylamine. …”
Section: Potential Energy Surfaces(pess) and Reaction Mechanisms On Tsupporting
confidence: 62%
“…5, the most favorable pathway for methylamine decomposition on Pt(100) can be described as H 3 CNH 2 / H 2 CNH 2 + H / H 2 CNH + 2H / HCNH + 3H / HCN + 4H / CN + 5H / CN + 5/2H 2 (g), and the production of CN by decomposition is consistent with the experimental ndings. 18 It is noteworthy that in methylamine decomposition on Pt(100) the C-N bond is not dissociated, which is the same as on Pd(111) 29 and different from on 2N-Mo(100) 28 and Ru(0001). 30 Moreover, the mechanism for methylamine decomposition is the same on Pt(100) and Pd(111), and the intermediates produced in methylamine decomposition are H 2 CNH 2 , H 2 CNH, HCNH, HCN, HNC and CN.…”
Section: Decomposition Potential Energy Surface (Pes)mentioning
confidence: 98%
“…Although massive amounts of information involving the decomposition of methylamine have been provided through experimental investigation, the detailed catalytic decomposition mechanisms of methylamine are still not clear. Recently, theoretical investigations have been applied to reveal the adsorption congurations of possible species involved in methylamine decomposition and the relevant reactions on transition metal surfaces, such as Si, 23,24 Ni, 25,26 Mo, 27,28 Pd, 29 Ru, 30 Co, 31 and Pt 32 surfaces, and on a B 12 N 12 nanocage. 33 On Si(100), Kato et al 24 found that N-H bond scission is preferential to C-N bond scission for methylamine decomposition under milder conditions, because of the charge transfer from the surface to the N atom, which weakens the N-H bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Lv et al 24 carried out DFT modelling to understand the initial CH 3 NH 2 decomposition on Ni(111) and Ni(100), and found that CH 3 NH 2 scission sequence took place with the order of C-H > N-H > C-N. Moreover, they investigated CH 3 NH 2 decomposition on Mo(100) 25,26 and Pd(111), 27 and the results showed that the most likely decomposition pathway was CH 28 and Co(111), 29 and found that the reaction mechanism of the hydrogenation pathway on both surfaces was HCN / CNH 2 + HCNH / CH 2 NH / CH 2 NH 2 + CH 2 NH / CH 3 NH 2 . Platinum is an effective catalyst for the Andrussow and Degussa processes, 5,30,31 and the Pt(111) surface is oen considered because this most stable surface dominates in small particles used in catalysts.…”
Section: Introductionmentioning
confidence: 99%